Characterization of a Peruvian isolate of Metarhizium anisopliae var. acridum, a pathogen of grasshoppers - Magalhães, Bonifácio Peixoto; Tigano, Myrian Silvana; Martins, Irene; Frazão, Heloisa; Ramirez, Hilda Gómez (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this study was to characterize the Peruvian isolate of Metarhizium anisopliae var. acridum, CG 863, obtained from the grasshopper Schistocerca interrita, a crop pest in Peru. The characterization was done by comparing this isolate with two other ones of M. anisopliae var. acridum, from Brazil and Australia, and with an isolate of M. anisopliae var. anisopliae. The three M. anisopliae var. acridum isolates had similar growth profiles in agar plates at 25°C and 37°C, and similar RAPD patterns according to the analysis of three primers. However, regarding these parameters and conidial size, these isolates were very distinct when compared to M. anisopliae var. anisopliae isolate. Bioassays indicated that the Peruvian isolate is as pathogenic as the Brazilian isolate against nymphs of Rhammatocerus schistocercoides.